Negative feedback concept in tagging: Ghost tags imperil the long-term monitoring of fishes - Šmejkal, Marek; Bartoň, Daniel; Děd, Vilém; Souza, Allan T; Blabolil, Petr; Vejřík, Lukáš; Sajdlová, Zuzana; Říha, Milan; Kubečka, Jan (PloS one, 2020)
Wildlife monitoring using passive telemetry has become a robust method for investigating animal migration. With increased use, this method progressively pollutes the environment with technological waste represented by so called ghost tags (PIT tags ending in the environment due to reproductive expulsions, shedding or animal mortality). However, their presence in the environment may lead to failed detections of living individuals. We used tagging data from studies of the asp Leuciscus aspius and the bleak Alburnus alburnus collected from 2014 to 2018 and located ghost tag positions on the monitored spawning site using portable backpack reader for their detection. We modelled virtual river-wide flat-bed antennas (widths 0.2, 0.4, 0.6 and 0.8 m) representing monitoring effort and estimated the probability of the presence of ghost tags within the antenna field. Of 3724 PIT tags used in the study, we detected on the spawning ground 173 ghost tags originating from long-term monitoring. The ghost tags accumulated in the environment in time, suggesting insufficient degradation rate or shift downstream from the research site. Number of ghost tags present on the spawning ground led to high probability of disabled readings of tagged fish passing through the antenna electro-magnetic field. We demonstrate how accumulated ghost tags may cause detection failures for focal species and incomplete data acquisition. We infer that intensive long-term monitoring using PIT tag technology may encumber future data acquisition or entail additional costs for clean-up.
Keywords: Animals; zpětná vazba; migrace zvířat; Cypriniformes; technologie dálkového snímání; Remote Sensing Technology; Feedback; Seasons; teoretické modely; zvířata; Animal Migration; máloostní; Models, Theoretical; roční období